Time Trends in Stroke and Subtypes Mortality Attributable to Household Air Pollution in Chinese and Indian Adults: An Age-Period-Cohort Analysis Using the Global Burden of Disease Study 2019 - Ma, Yudiyang; Yang, Donghui; Bai, Jianjun; Zhao, Yudi; Hu, Qian; Yu, Chuanhua (Frontiers in Aging Neuroscience, 2022)
Household air pollution (HAP) exposure is recognized as a major health concern in areas relied on residential burning of solid fuels for cooking and heating. However, previous study has focused on mortality across time and reported changes in age-specific mortality globally but failed to distinguish cohort from period effects. Therefore, this study aimed to differentiate the relative contributions of period and cohort effects to overall time trends of HAP-attributable stroke mortality between the most presentative East and South Asia countries. Data were obtained from the Global Burden of Disease (GBD) database. The age, period, and cohort effects were estimated using the age-period-cohort (APC) model. The overall age-standardized mortality rates (ASMRs) of stroke in China decreased by 39.8% compared with 35.8% in India, while stroke subtypes in both the sexes and countries showed consecutive significant declines from 1990 to 2019. The age-specific and cohort-specific HAP-attributable stroke mortality declined over time in China and India. By APC analysis, substantially increasing age effects were presented for stroke and subtypes from 25 to 84 years. China had a rapid reduction in the independent period and cohort effects. Also, the risk of death for subarachnoid hemorrhage (SAH) had the most striking decline for both sexes in period and cohort effects. Reductions of India were less favorable than China, but the independent period and cohort effects progressively decreased during the entire period for both the sexes. Males experienced a slightly higher mortality risk than females in both countries. Although prominent reductions were observed in HAP-attributable stroke and subtypes mortality during the past 30 years, China and India still suffered uneven HAP-attributable stroke burden. Thus, it is of high significance to introduce advanced solid fuels replace technology and knowledge regarding clean fuel use.